English for cabin crew - Ellis, Sue. (Oxford, United Kingdom : Oxford University Press, 2010)
Quick course for flight attendants who need to use English on the ground or in the air. It's also suitable for students who are interested in a career in cabin service and are preparing for an entry test or interview with an airline.